(untitled) (Research, Society and Development, 2020)
Objective: understand the experience of maternal singing in the mother-baby relationship in the context of child development. Method: qualitative research conducted through semi-structured interview with 15 women mothers captured in a pediatric outpatient clinic of a university hospital in the city of Rio de Janeiro, conducted in the first semester of 2019. Results: from the thematic-categorical analysis, two categories emerged: Maternal feelings and attitudes in the relationship with the baby child and Maternal singing in the context of baby care. Conclusion: singing for the child is involved in psycho-affective aspects, but also in the family and social aspects of the mother woman to take care of the child, in situations of playing, sleeping or comforting. It is an important communication tool in the mother-baby relationship that needs to be valued by health professionals in the context of child development.